PERSEPSI WAJIB PAJAK DI KOTAMADYA PONTIANAK ATAS PERATURAN PEMERINTAH NO. 46 TAHUN 2013 - B41111160, Dwi Handoyo (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This study was conducted to determine the perception of the taxpayer on Government Regulation No.46 that force since July 2013. The researchers used primary data in the form of questionnaires distributed to the respondents as a taxpayer who is an enterprenuer or owner of Micro, Small and Medium businesses in Pontianak City. Researchers used several indicators to measure the Perceptions of The Taxpayer, The Ease of Calculating Tax, The Socialization of The Tax and Sanctions of Taxation. The results showed that the taxpayer has a positive of government regulation No.46 which will encourage taxpayer to make a tax reporting. This indicates that the purpose of these regulations to provide ease of calculating taxes and increase income tax revenue of business can be achieved. Some things to note is the lack of socialization of the tax and the consistency of enactment of tax penalty. Direktorat Jendral Pajak (DJP) and KPP Pratama are expected to make this study as an input in improving service to the community. Keyword :       Taxpayer Perceptions, Socialization, Sanctions of Taxation, and Tax Reporting.